CTNND2—a candidate gene for reading problems and mild intellectual disability. Issue 2 (3rd December 2014) - Hofmeister, Wolfgang; Nilsson, Daniel; Topa, Alexandra; Anderlid, Britt-Marie; Darki, Fahimeh; Matsson, Hans; Tapia Páez, Isabel; Klingberg, Torkel; Samuelsson, Lena; Wirta, Valtteri; Vezzi, Francesco; Kere, Juha; et al.
Abstract : Background: Cytogenetically visible chromosomal translocations are highly informative as they can pinpoint strong effect genes even in complex genetic disorders. Methods and results: Here, we report a mother and daughter, both with borderline intelligence and learning problems within the dyslexia spectrum, and two apparently balanced reciprocal translocations: t(1;8)(p22;q24) and t(5;18)(p15;q11). By low coverage mate-pair whole-genome sequencing, we were able to pinpoint the genomic breakpoints to 2 kb intervals. By direct sequencing, we then located the chromosome 5p breakpoint to intron 9 of CTNND2 . An additional case with a 163 kb microdeletion exclusively involving CTNND2 was identified with genome-wide array comparative genomic hybridisation. This microdeletion at 5p15.2 is also present in mosaic state in the patient's mother but absent from the healthy siblings. We then investigated the effect of CTNND2 polymorphisms on normal variability and identified a polymorphism (rs2561622) with significant effect on phonological ability and white matter volume in the left frontal lobe, close to cortical regions previously associated with phonological processing. Finally, given the potential role of CTNND2 in neuron motility, we used morpholino knockdown in zebrafish embryos to assess its effects on neuronal migration in vivo. Analysis of the zebrafish forebrain revealed a subpopulation of neurons misplaced between the diencephalon and telencephalon. Conclusions: Taken together, our human genetic and in vivo data suggest that defective migration of subpopulations of neuronal cells due to haploinsufficiency of CTNND2 contribute to the cognitive dysfunction in our patients.